HUBUNGAN ASUPAN MAKAN, PERSEPSI CITRA TUBUH, DAN PERILAKU PENGENDALIAN BERAT BADAN DENGAN STATUS GIZI GURU DI PERGURUAN MUHAMMADIYAH RAWAMANGUN - Azizah, Fina Nailatul; Rahayu, Leni Sri (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Overnutrition is one of the most common nutritional problems in the adult age group. Overnutrition among working adults can harm productivity at work. This is because excess nutritional status can cause various non-communicable diseases such as type 2 diabetes mellitus, coronary heart disease, and cancer. The purpose of this study was to determine the relationship between food intake, body image perception, and weight control behavior with nutritional status at the Muhammadiyah College of Rawamangun. The research was conducted in August 2023, involving 61 teachers. The research method used is quantitative research with a cross-sectional design and total sampling method for sample selection. Data was analyzed using the Chi-Square statistical test. Dietary intake was measured using a 2x24-hour recall method, body image perception and weight control behavior were assessed using Body Shape Questionnaire (BSQ) Short Version also waist circumference, body weight and height were measured using anthropometric measurements. The results of data analysis indicate a significant relationship between energy intake, protein intake, fat intake, carbohydrate intake, body image perception, and weight control behavior with nutritional status based on BMI and waist circumference (P<0.05). However, no significant relationship was found between body image perception and weight control behavior with nutritional status based on waist circumference (p>0.05). In conclusion, there were significant relationship between energy intake, protein intake, fat intake, carbohydrate intake, body image perception, and weight control behavior with nutritional status based on BMI and waist circumference.